Studi Literatur Pengaruh Transfer Pricing dan Good Corporate Governance terhadap Penghindaran Pajak - OktaAzrul Ananda; Aris Eddy Sarwono; Fadjar Harimurti (Pusat Riset dan Inovasi Nasional, 2025)
Abstract. This study aims to analyze the influence of transfer pricing practices and good corporate governance (GCG) on tax avoidance among companies listed in Indonesia. Transfer pricing is a strategy commonly employed by multinational corporations to shift profits to jurisdictions with lower tax rates in order to minimize tax liabilities. Meanwhile, GCG serves as a supervisory mechanism that can mitigate tax avoidance through the implementation of transparency, accountability, and strong internal controls. This research adopts a literature review approach by examining relevant previous studies to explore the relationship between the two variables and tax avoidance. Some studies reveal that transfer pricing has a significant impact on tax avoidance, while the effectiveness of GCG largely depends on the quality of implementation and the strength of a company’s internal governance. Therefore, integrating tax efficiency strategies with robust corporate governance is essential to balance compliance and the optimization of tax burdens.